Sexually opposite effects of testosterone on mating success in wild rock hyrax. (31st July 2019) - Koren, Lee; Weissman, Yishai; Schnitzer, Inbar; Beukeboom, Rosanne; Bar Ziv, Einat; Demartsev, Vlad; Barocas, Adi; Ilany, Amiyaal; Geffen, Eli
Abstract: Although males and females share traits, their motivations and needs may be different, due to life-history disparities that lead to divergent selection pressures. Proximate mechanisms underlying differences between the sexes include hormones that mediate the development and activation of suites of traits. Testosterone is associated with morphological features, physiological processes, and social behaviors in both sexes. However, even if present in similar concentrations in the circulation, testosterone often affects males and females differently. We combined behavioral mating observations of the wild polygynandrous rock hyrax ( Procavia capensis ) with hair testosterone that represents long-term integrated levels. We found that whereas copulation success increases with the rise in testosterone in males it decreases in females. We did not find an association between testosterone and choosiness in either sex. However, we found that males with higher testosterone mate-guarded females with lower testosterone. Our findings show disassortative mating and mate-guarding in respect to testosterone and provide clues to the cost of testosterone for females, in terms of copulation success. These results open up intriguing questions relating to the role of testosterone in mediating a similar trade-off in male and female reproductive success. Abstract : Both sexes have testosterone, which is associated with morphology, physiology, and behavior. We combined mating observations of the wild rock hyrax with testosterone measures and found that while males with higher testosterone copulate more, it is the opposite in females. Testosterone was not related to choosiness in either sex, but males with higher testosterone mate-guarded females with lower testosterone. Our findings open up intriguing questions relating to the role of testosterone in females.